A Review of Psychosocial Models for the Development of Musculoskeletal Disorders and Common Psychosocial Instruments - , Kuok Ho Daniel Tang (Archives of Current Research International, 2020)
Aims: While the biomechanical factors causing musculoskeletal disorder (MSDs) are well defined, the psychosocial dimension of MSDs is complex and affected by personal, organizational and environmental elements. There is an impetus to understand how psychosocial risk factors contribute to the manifestation of MSDs and systematically present the strengths and constraints of various instruments in assessing psychosocial risk factors. Study Design: This article critically reviews various models linking psychosocial constructs to MSDs and various instruments for evaluating psychosocial risk factors. Methodology: This article reviews the most pertinent literature which presents and discusses the connection of psychosocial domains with the development of MSDs as well as the common instruments used for evaluation of psychosocial factors. Results: It shows an intricate connection between psychosocial and biomechanical aspects compounded by organizational, individual and environmental factors. Psychosocial factors particularly psychological demand, decisional latitude, level of social support and work organization result in stress which produces strain and physiological deterioration hence MSDs. Different psychosocial risk factors have also been found to evoke MSDs in different body parts. Overarching cognitive and psychological aspects consisting of work demands, maneuver margins and work recognition have also been proposed in examining the psychosocial dimension of MSDs. Instruments for measuring psychological constructs are often subjective and rely on personal reflections. Some instruments assess multiple psychosocial factors while other assess specific attributes. There instruments share a common shortcoming of treating risk factors across different workplaces as homogenous. Conclusion: Refinement of the instruments and development of sector-specific instruments are beneficial for more reliable evaluation of psychosocial risk factors.